ACADEMIC LITERACY AND WRITING IN UNIVERSITY: FROM THEORY TO PRACTICE - Yuldasheva Rano Juraevna (Journal of Higher Education and Academic Advancement, 2024)
The author examines the problem of developing students' academic literacy and teaching writing from the perspective of theory and practice. The article analyzes the nature and structure of academic literacy and puts forward the thesis that the formation of academic literacy is based on the concept of academic discourse. Written language is seen as a key component of academic literacy, and teaching writing is built on learning to translate academic written discourse.